New Classification for Bifurcated Mandibular Neural Canal - Wang, Xiang; Yang, Hao; Wu, Yue; Shao, Zifei; Hong, Pengyu; Hu, Yanjia; Li, Kun (International Journal of Human Anatomy, 2022)
Objectives To analyze the occurrence rate of bifurcated mandibular canal (BMC) by cone beam CT(CBCT) and summarise a new classification for further clinical work and academic communication. Method Randomly collected the CBCT images of 350 adult patients. Firstly, we analysed and summarized the BMCs into four types by the position of bifurcation point in the mandible. Second, we did statistics about occurrence. Then we have measured three kinds of distance of Type I and Type II. At last, we compared the advantages and disadvantages about different classifications. Results Among these 350 patients, we found 110 adult people with BMC which indicated the occurrence rate of BMC was 31.43%. The most common type was Type I, especially Type IB, and the least was Type III. Vertical distance between the apex of the second molar, the third molar and mandibular canal are 4.36±2.51 mm and 2.45±2.23 mm. Distance from the apex of two molars to the bifurcated spot are 15.87±6.82mm and 9.32±5.37mm. And the distance between the apex and retromolar foramen in Type I are 22.19±5.97mm and 15.82±4.68mm. Conclusion Comparing with former typing theory, we summarized a new classification which is simpler and more convenient, which should attach scholars’ attention to BMC during clinical work.
Keywords: BMC; Classification; CBCT